Characterization of wind turbine flow through nacelle-mounted lidars: a review - Letizia, Stefano; Brugger, Peter; Bodini, Nicola; Krishnamurthy, Raghavendra; Scholbrock, Andrew; Simley, Eric; Porté-Agel, Fernando; Hamilton, Nicholas; Doubrawa, Paula; Moriarty, Patrick (Frontiers in Mechanical Engineering, 2023)
This article provides a comprehensive review of the most recent advances in the planning, execution, and analysis of inflow and wake measurements from nacelle-mounted wind Doppler lidars. Lidars installed on top of wind turbines provide a holistic view of the inflow and wake characteristics required to characterize and optimize wind turbine performance, carry out model validation and calibration, and aid in real-time control. The need to balance the enhanced capabilities and limitations of lidars compared to traditional anemometers inspired a broad variety of approaches for scan design and wind reconstruction, which we discuss in this review. We give particular emphasis to identifying common guidelines and gaps in the available literature with the aim of providing an exhaustive picture of the state-of-the-art techniques for reconstructing wind plant flow using nacelle-mounted lidars.